Effectivenes of Group Counseling with People-Centered Approach to Improve Student’s social skills - Larassati, Rini (COUNS-EDU: The International Journal of Counseling and Education, 2018)
Humans are social beings who can not live alone and always have relationships with others. Each individual is expected to be able to relate well with other individuals in order to fulfill social needs. Fulfillment of good relationships with others requires skills of social skills. However, in reality there are still students who do not have good social skills. Therefore, the purpose of this study was to determine the effectiveness of group counseling with a person centered approach to students' social skills. The method used is quasi experimental research with non-equivalent control group design. The research was conducted in SMP Negeri 8 Yogyakarta with sample of 10 students of class VII. The instrument used in this study is the scale of social skills. Data analysis technique using wilcoxon test. The results showed that group counseling with a person centered approach was effective on the students' social skills.